Reproductive Senescence in Two Lemur Lineages - Kappeler, Peter M.; Pethig, Leonie; Prox, Lea; Fichtel, Claudia (Frontiers in Ecology and Evolution, 2022)
The relationship between age and reproductive performance is highly variable across species. Humans and some cetaceans exhibit an extreme form of reproductive ageing in that female reproduction ceases years or even decades before average life expectancy is reached. However, neither the existence of reproductive senescence in some taxa nor its absence in others is fully understood. Comparative data from other long-lived mammals may contribute to a more comprehensive understanding of the evolution of menopause, but data from wild primates, in particular, are scarce. We therefore investigated age-related female reproductive performance in two wild sympatric populations of Malagasy primates: Verreaux’s sifakas (Propithecus verreauxi) and redfronted lemurs (Eulemur rufifrons), which have a maximal longevity of more than 20 years. Based on 25 years of long-term demographic data, we extracted information on reproductive output of 38 female Verreaux’s sifakas and 38 female redfronted lemurs of known age. We modelled variation in female reproductive performance and interbirth intervals as a function of age, the number of adult females to account for female competition, and rainfall as a proxy for annual variation in food availability. We also compared our results for these two species with data on captive populations of the same two genera that are buffered from fluctuations in environmental variables. Our analyses disclosed evidence for reproductive senescence in three out of four populations (captive Coquerel’s sifakas, wild redfronted lemurs and captive red lemurs) and a strong trend for wild Verreaux’s sifakas. Compared to wild populations, reproductive ageing was therefore not less pronounced in captive animals, even though the latter are buffered from external adversities. In wild redfronted lemurs, mothers were more likely to give birth in years with more rainfall, but neither the number of co-resident females, nor annual rainfall did predict variation in the probability of giving birth in wild Verreaux’s sifakas. Thus, our study contributes valuable comparative information on reproductive senescence in a basal group of primates, and offers insights into the modulating effects of environmental, social and phylogenetic factors on patterns and dynamics of age-specific female reproduction.